PROSES PENYIDIKAN DALAM UPAYA PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PEREDARAN VCD DVD PORNO DI WILAYAH HUKUM POLRESTA SAMARINDA - Dina Paramitha Hefni Putri (Universitas 17 Agustus 1945 Samarinda, 2018)
The formulation of the problem is how the modus operandi in circulationpornographic VCD DVD by actors, how the investigation process and theconstraints faced by the investigator and how efforts to control thecirculation of pornographic DVD VCD carried out by the PoliceSamarinda. In this case study method used by the author is empirical legalresearch, conducted research at Police Samarinda and Samarindajurisdictions whose purpose is to describe and analyze the modusoperandi by the perpetrators, constraints investigation and efforts incombating trafficking in pornographic DVD VCD Polresra Samarinda.List of reference in the this thesis is Law No. 2 of 2002 on the IndonesianNational Police, Law No. 44 Year 2008 on Pornography and the Code ofPenal (Penal Code).